Osteochondral lesion of the talus: possible treatment options for Thailand - Rasamimongkol, Supachok; Tangsripong, Piroon (Asian Health, Science and Technology Reports, 2018)
Osteochondral defects (OCDs) of the talus is a broad term used to describe an injury or abnormality of the talar cartilage and adjunct bone. The treatment options vary from non-surgical treatment to a variety of surgical treatments depending on patient signs and symptoms. This review aims to provide an overview of treatment strategies that could be made available in Thailand. The pros and cons of several techniques including conservative treatment, fixation, microfracture, OAT and antegrade or retrograde drilling are discussed. We also provide suggestions for future development in OCDs of the talus care.